A CRISPR Path to Finding Vulnerabilities and Solving Drug Resistance: Targeting the Diverse Cancer Landscape and Its Ecosystem. Issue 4 (9th November 2022) - McLean, Benjamin; Istadi, Aji; Clack, Teleri; Vankan, Mezzalina; Schramek, Daniel; Neely, G. Gregory; Pajic, Marina
Abstract: Cancer is the second leading cause of death globally, with therapeutic resistance being a major cause of treatment failure in the clinic. The dynamic signaling that occurs between tumor cells and the diverse cells of the surrounding tumor microenvironment actively promotes disease progression and therapeutic resistance. Improving the understanding of how tumors evolve following therapy and the molecular mechanisms underpinning de novo or acquired resistance is thus critical for the identification of new targets and for the subsequent development of more effective combination regimens. Simultaneously targeting multiple hallmark capabilities of cancer to circumvent adaptive or evasive resistance may lead to significantly improved treatment response in the clinic. Here, the latest applications of functional genomics tools, such as clustered regularly interspaced short palindromic repeats (CRISPR) editing, to characterize the dynamic cancer resistance mechanisms, from improving the understanding of resistance to classical chemotherapeutics, to deciphering unique mechanisms that regulate tumor responses to new targeted agents and immunotherapies, are discussed. Potential avenues of future research in combating therapeutic resistance, the contribution of tumor–stroma signaling in this setting, and how advanced functional genomics tools can help streamline the identification of key molecular determinants of drug response are explored. Abstract : Improving the understanding of how tumors evolve following therapy and the molecular mechanisms underpinning de novo or acquired resistance is critical to identifying new targets and to develop more effective combination regimens. Current and potential future applications of functional genomics tools to characterize dynamic cancer resistance mechanisms to both conventional and new targeted agents and immunotherapies are discussed.